Effect of processing and oil type on carotene bioaccessibility in traditional foods prepared with flour and puree from orange-fleshed sweetpotatoes - Chilungo, S.; Muzhingi, T.; Truong, V.D.; Allen, J.C. (Wiley, 2019)
Consumption of Orange‐Fleshed sweetpotato (OFSP) and products as source of provitamin A is being promoted to tackle vitamin A deficiency (VAD) in sub‐Saharan Africa. However, limited information is available on β‐carotene retention in foods and delivery after digestion. The study assessed carotene retention and bioaccessibility following in vitro digestion on traditional foods having OFSP among the ingredients. Sunflower oil, margarine and beef fat were evaluated on their effect on β‐carotene bioaccessibility. Porridge and chapatis were prepared with either OFSP puree or flours in the formulations. Carotene retention was highest in chapatis (83%) as compared to porridge (65%). Micerallisation efficiency of all‐trans β‐carotene was comparable between similar products but greater in chapatis (62%) than porridge (11%). Sunflower oil had the highest all‐trans β‐carotene bioaccessibility compared to margarine and beef fat. The results support the promotion of consumption of OFSP‐based products as good source of provitamin A to fight VAD.